Pengaruh Leverage, Likuiditas, Dan Profitabilitas Terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2015-2021) - Nurul Hikmah; Endang Mahpudin (Peneliti.net, 2023)
Taxes are the country's largest revenue which is very important. This is because most of the infrastructure and needs of other countries use taxes. This study aims to obtain evidence of the effect of leverage, liquidity, and profitability on tax aggressiveness of telecommunications companies listed on the Indonesia Stock Exchange (IDX) 2015-2021. In this study the independent variables are leverage, liquidity, and profitability. While the dependent variable is tax aggressiveness. This study used a purposive sampling method. And the number of samples of this research is 42 samples. This study uses linear regression to determine the effect of independent variables on tax aggressiveness. The results of this study indicate that the leverage variable has a negative effect, while liquidity has a positive effect and profitability has a positive effect on tax aggressiveness.